Survival benefit of induction chemotherapy in treatment for locally advanced nasopharyngeal carcinoma – A time-to-event meta-analysis. Issue 8 (August 2015) - Song, Yaqi; Wang, Wanwei; Tao, Guangzhou; Zhou, Xilie
<x xml:space="preserve">Abstract</x> Highlights Use the follow-up data as a time-to-event data for this meta-analysis. Updata relevant Chinese and English language literature until January 2015. Show that plus IC into CCRT may reduce the progression and metastasis in LANPC.